Metabolic Engineering of Yarrowia lipolytica for Zeaxanthin Production - Zhang, Guilin; Chen, Jing; Wang, Yongzhen; Liu, Zhen; Mao, Xiangzhao (Journal of agricultural and food chemistry, 2023)
Zeaxanthin is a carotenoid, a dihydroxy derivative of β-carotene. Zeaxanthin has antioxidant, anti-inflammatory, anticancer, and neuroprotective properties. In this study, Yarrowia lipolytica was used as a host for the efficient production of zeaxanthin. The strain Y. lipolytica PO1h was used to construct the following engineered strains for carotenoid production since it produced the highest β-carotene among the Y. lipolytica PO1h- and Y. lipolytica PEX17-HA-derived strains. By regulating the key nodes on the carotenoid pathway through wild and mutant enzyme comparison and successive modular assembly, the β-carotene concentration was improved from 19.9 to 422.0 mg/L. To provide more precursor mevalonate, heterologous genes mvaE and mvaSMT were introduced to increase the production of β-carotene by 27.2% to the yield of 536.8 mg/L. The β-carotene hydroxylase gene crtZ was then transferred, resulting in a yield of zeaxanthin of 326.5 mg/L. The oxidoreductase RFNR1 and CrtZ were then used to further enhance zeaxanthin production, and the yield of zeaxanthin was up to 775.3 mg/L in YPD shake flask.Zeaxanthin is a carotenoid, a dihydroxy derivative of β-carotene. Zeaxanthin has antioxidant, anti-inflammatory, anticancer, and neuroprotective properties. In this study, Yarrowia lipolytica was used as a host for the efficient production of zeaxanthin. The strain Y. lipolytica PO1h was used to construct the following engineered strains for carotenoid production since it produced the highest β-carotene among the Y. lipolytica PO1h- and Y. lipolytica PEX17-HA-derived strains. By regulating the key nodes on the carotenoid pathway through wild and mutant enzyme comparison and successive modular assembly, the β-carotene concentration was improved from 19.9 to 422.0 mg/L. To provide more precursor mevalonate, heterologous genes mvaE and mvaSMT were introduced to increase the production of β-carotene by 27.2% to the yield of 536.8 mg/L. The β-carotene hydroxylase gene crtZ was then transferred, resulting in a yield of zeaxanthin of 326.5 mg/L. The oxidoreductase RFNR1 and CrtZ were then used to further enhance zeaxanthin production, and the yield of zeaxanthin was up to 775.3 mg/L in YPD shake flask.